2015
DOI: 10.1111/1745-9125.12078
|View full text |Cite
|
Sign up to set email alerts
|

Delinquency and Gender Moderation in the Moving to Opportunity Intervention: The Role of Extended Neighborhoods

Abstract: A long history of research has indicated that neighborhood poverty increases youth's risk taking and delinquency. This literature predominantly has treated neighborhoods as independent of their surroundings despite rapidly growing ecological evidence on the geographic clustering of crime that suggests otherwise. This study proposes that to understand neighborhood effects, investigating youth's wider surroundings holds theoretical and empirical value. By revisiting longitudinal data on more than 1500 low‐income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
50
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 74 publications
9
50
2
Order By: Relevance
“…Net of their own sociodemographic characteristics and the level of socioeconomic disadvantage in their neighborhoods, youth are less likely to offend when their neighborhood is surrounded by disadvantaged neighborhoods; hence, they are more likely to offend when their neighborhood is surrounded by comparatively affluent neighborhoods. This effect is consistent with the hypothesis derived from relative deprivation and criminal opportunity theories and with recent research on the influence of extended neighborhood disadvantage on offending using non‐nationally representative samples of youth and different analytical strategies (e.g., Graif, )…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Net of their own sociodemographic characteristics and the level of socioeconomic disadvantage in their neighborhoods, youth are less likely to offend when their neighborhood is surrounded by disadvantaged neighborhoods; hence, they are more likely to offend when their neighborhood is surrounded by comparatively affluent neighborhoods. This effect is consistent with the hypothesis derived from relative deprivation and criminal opportunity theories and with recent research on the influence of extended neighborhood disadvantage on offending using non‐nationally representative samples of youth and different analytical strategies (e.g., Graif, )…”
Section: Resultssupporting
confidence: 90%
“…Consistent with this theme, recent research by Odgers and colleagues () has shown that low‐income boys in Great Britain who grew up close to affluent peers displayed higher levels of delinquency than did low‐income boys who lived in areas characterized by concentrated poverty. Graif's () finding that impoverished boys who live in high‐poverty areas surrounded by low‐poverty neighborhoods report higher levels of delinquency than those who live in areas of concentrated economic disadvantage also supports this contention. Thus, low levels of disadvantage in extralocal neighborhoods may increase delinquent behavior as adolescents are constantly reminded of their situation relative to nearby neighborhoods in the broader community.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Omitting information about spatial relationships may also cost researchers in terms of their substantive findings. For example, evidence suggests that poor neighborhood surrounded by other poor neighborhoods affect people differently than do poor neighborhoods surrounded by less disadvantaged areas (Graif, 2015). In addition to modeling relationships among level 2 neighborhood units, researchers should consider whether higher-level geographies should also be incorporated into their models.…”
Section: Discussionmentioning
confidence: 99%
“…An emerging theme from this literature is the importance of neighborhoods' spatial contexts, whether measured in terms of adjacency or distance to other neighborhoods, or conceptualized as activity spaces or other extended neighborhood contexts (Graif 2015, 2016). For example, Patillo (Pattillo-McCoy, 1999) brings to light important evidence that social mobility among Chicago's black middle class is undermined by spatial proximity to pockets of concentrated poverty and crime.…”
mentioning
confidence: 99%